KEPUTUSAN PENGGUNAAN E-WALLET SEBAGAI ALAT TRANSAKSI DIGITAL: SEBUAH KAJIAN LITERATUR 2012-2023 - Banutama, Berty; Hatta, Atika Jauharia; Biyanto, Frasto; Kristiana, Deranika Ratna (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2024)
The use of e-wallets as a digital transaction tool has become a rapidly growing phenomenon in recent years. E-wallets offer various conveniences and benefits that encourage widespread adoption among consumers. This literature study aims to identify and analyze the factors that influence the decision to use e-wallets as a digital transaction tool. The research method used in this literature study is based on a review of 30 previous research articles, published in the period 2012-2023. The articles reviewed include publications from within and outside the country, with domestic articles indexed by Sinta and international articles indexed by Scopus. From this literature study, it was concluded that the main factors that influence the decision to use e-wallets as a digital transaction tool are ease of use, usefulness, security, social influence, performance expectancy, facilitating conditions, habits, hedonic motivations, effort expectancy, financial literacy, promotion, risk, price value, and trust. Meanwhile, the theories most widely used to explain this phenomenon are TAM and UTAUT. Implication of this research is providing insight for researcher to make it easier to find research gaps that have not been explored much in this field.